Kinetics of flax polysaccharides enzymatic hydrolysis by Trichoderma viride xylanase. - Е. V. Оzhimkova (Тонкие химические технологии)
The present work is devoted to kinetics of flax polysaccharides enzymatic hydrolysis by Trichoderma viride xylanase study.